EXPRESSING DISAGREEMENT IN ACADEMIC SETTINGS CONDUCTED BY EFL LEARNERS :A case Study of Post Graduate Program in English of UPI - Andriyani, Yeni (2006)
This present study was designed as an attempt to examine the types and strategies used by EFL learners in expressing disagreement in academic setting. The observations of EFL students' activities in the classroom were conducted to explore kind of strategies of uttering disagreement, factors which influence the variations in the realizations of the strategies namely: Age, Gender, Institutional Based Power and Social Distance.Data for this descriptive study were gained through three month of observations. The emic perspectives were used in order to gain in depth description and information about speech act of disagreement in a very natural setting. The data collection was done by taking the field notes; transcribing the interviews, and videotaping the classroom activities.The study found that the lecturer's types of disagreements ranged from Mitigated Disagreement (indirect) to Strong Disagreement (direct) and he also performed both discursive pattern of politeness namely deductive and inductive pattern. On the other hand, the students' type of expressing disagreement ranged from "strong-yet-mitigated" to "mitigated" and correlate with contextual variables he/ she possessed. In the classroom setting, for the lecturer, institutional power did not correlate greatly with degree of directness expressed in his disagreement strategy. Whether the students' disagreement types, it became the fact that strategies of disagreement they performed were greatly influenced by the contextual variables of politeness. The study also found that the act of expressing politeness is influenced by age. It was found that when talking to an interlocutor of different age, a speaker would indicate different preferences at using strategies. The contextual variables namely institutional power and social distance had also influenced greatly of the speakers in expressing disagreements. The respondents put awareness to his/ her interlocutor status in power and social distance. The less power and social distance between the members of communication transaction, the more direct the utterance of disagreement would be.The present study concludes that the strategies used in expressing disagreement varied in two different types of politeness that reflected in the two different disagreement discourse pattern. This study also showed that the strategies of disagreement seemed to be influenced by characteristics of responses given by the respondents in relation to their contextual variables. It was hoped that the findings of this study would assist in deciding whether or not to implement the types of disagreement conducted by both students and lecturer. Furthermore, this study may also inspire other researchers to conduct research, which take different settings, levels of education, or background, in another issue in Pragmatics.